Nine lives and alibis - Conte, Cate (Conte, Cate. Cat Cafe mystery, 2023)
It's October in Daybreak Harbor, which means everything Halloween. The town is going all out for the holiday, hoping to one-up the festivities in neighboring Salem, Massachusetts, and Maddie James is delighted to be part of the planning for the annual happenings. But trouble brews when Maddie's youngest sister, Sam, books a famous medium, Balfour Dempsey, to come to town for the celebrations and stay in the local haunted inn--along with his equally famous black cat. The town busybody books a secret reading with Balfour and doesn't want anyone to know why. Maddie's best friend Becky is hell-bent on getting Balfour to help her solve two 40-year-old mysteries--a murder and a missing maid. And the psychic has a stalker who's followed him here to the island, demanding he connect with her dead husband. When Balfour is pushed off the cliffs behind the inn to his death and his beloved cat goes missing, it throws the whole town into a frenzy. And Maddie and her family find themselves in the middle of a murder mystery straight out of a Halloween movie.